2012
DOI: 10.1063/1.4757066
|View full text |Cite
|
Sign up to set email alerts
|

Electronic excitations of C60 fullerene calculated using the ab initio cluster expansion method

Abstract: The electronic excited states and optical absorption spectrum of C(60) fullerene below 6.2 eV (200 nm) were calculated using the ab initio many-body wavefunction theory of cluster expansion method: the symmetry-adapted cluster-configuration interaction method. Not only optically allowed states but also optically forbidden states were calculated for studying the observed weak absorptions in the visible region. The lowest calculated singlet excited state was the 1(1)G(g) state. The electron correlation effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The band gap of C 60 measured in films is 1.7 eV 144 (0.062 hartree) and in liquids 1.82 eV 138 (0.067 hartree), values that agree fairly well with the separation between the HOMO and the LVVO (or C 60 's very similar valence LCMO) for both pure DFAs, an indication that both the occupied and empty orbital have the same "DFA upshift". Clearly, research into more meaningful eigenvalues from DFA calculations is important but is not the central theme of this paper, which is concerned with the separation of the empty orbital space into valence and nonvalence orbitals.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The band gap of C 60 measured in films is 1.7 eV 144 (0.062 hartree) and in liquids 1.82 eV 138 (0.067 hartree), values that agree fairly well with the separation between the HOMO and the LVVO (or C 60 's very similar valence LCMO) for both pure DFAs, an indication that both the occupied and empty orbital have the same "DFA upshift". Clearly, research into more meaningful eigenvalues from DFA calculations is important but is not the central theme of this paper, which is concerned with the separation of the empty orbital space into valence and nonvalence orbitals.…”
supporting
confidence: 60%
“…The LCMO occurs at ε = −0.0232 hartree, has the correct t 1u symmetry, and is only slightly larger spatially than the LVVO which has a nearly identical pseudoeigenvalue. However, the rest of C 60 's unoccupied CMO level diagram consists of numerous diffuse orbitals and resembles a continuum starting at zero energy (see ref 138 for a typical C 60 CMO spectrum).…”
mentioning
confidence: 99%
“…Indeed, it is known that TDDFT sometimes underestimates the energy differences of low-lying excited states of conjugated systems with several degenerate states such as porphyrines and fullerenes. [25,27,28] In the following, we focus on the first three singlet excitations in pyridine, resulting from B3LYP/6-31 + + G** calculations. As the ground state is a singlet, only singlet excitations can have a non-zero oscillator strength.…”
Section: Ground State and Excited State Properties Of Pyridine And Nimentioning
confidence: 99%
“…The α‐band has very low intensity, while the intensity of the β‐band is very high. The SAC‐CI calculations for large PAH such as C 60 fullerene and extended coronenes have been reported; however, systematic studies on oligoacenes by the SAC‐CI have not been reported before, although the EOM‐CC study is available …”
Section: Resultsmentioning
confidence: 99%